Treaty Relations as a Method of Resolving Intellectual Property Issues (Final Report) - Michael Asch; Intellectual Property Issues in Cultural Heritage (Simon Fraser University, 2014)
The final report for "Treaty Relations as a Method of Resolving Intellectual Property Issues", an IPinCH Community Initiative.